Institutionalized elderly: decision and consequences in family relations - Figueiredo, Maria do Carmo Clemente Marques (2018)
This study aimed to identify the starting point for the institutionalization of the elderly, as well as the family relationship and the bond of affection between the elderly and their families after the institutionalization process. It was carried out through a descriptive exploratory field research, with a qualitative approach, carried out in a long - term institution for the elderly (ILPIs) in the Municipality of Santa Rita, PB. For the data collection, an interview was conducted guided by a semi-structured script. To interpret the data, Bardin's content analysis technique was used to identify two categories: "Institutionalization Option" and "Family Conviviality". The study identified that the option of asiling the elderly is related to the family, not being compacted with the elderly, and that the elderly interviewed do not maintain or maintain a relatively weak bond of affectivity with their families after the institutionalization process.